Screening of Ginger Germplasms Against Rhizome Rot Disease Complex in Mid Hill Condition of Nepal - Acharya, Basistha; Khadka, Ram B. (Journal of the Plant Protection Society, 2018)
Ginger (Zingiber officinale) is one of the major spice crops of Nepal. Rhizome rot disease complex is an important production constraint. The search of resistant source for this disease is still at infant stage in Nepal. In the present study, Forty-two ginger germplasm collected from different locations were screened against rhizome rot complex in sick plot of Ginger Research Programme, Kapurkot, Salyan during the ginger growing season of 2012/13-2013/14. The indicator such as percent disease incidence, fresh rhizome yield, diseased and healthy rhizome number were taken to evaluate the resistance and tolerance of the germ-plasms under optimum disease conditions. Varied level of resistance and tolerance were observed among the tested germplasms. The percent disease incidence was ranged from 22.76 to 71.99 % while healthy rhizome yield and diseased rhizome percentage was varied from 11.5 to 150 gm per plant and 2.4 % to 57.85% respectively. Out of the 42 germplasms screened against rhizome rot disease complex, none of them was found to be resistant and moderately resistant however, 20 moderately susceptible (PDI-21 to 50 % ) and 22 highly susceptible (PDI - above 50 %) were recorded. Germ-plasm ZI 1017 was found to be comparatively resistant with lowest percentage disease incidence (22.76%), highest healthy rhizome per plant (101.1gm) and lowest diseased rhizome yield percentage (4.36%).